The Effect Of Training And Development on Employee Performance With Mediation of Employee Satisfaction - Hadaitana, Dini; M.Ali Iqbal (Green Publisher, 2023)
Employees are one of the most critical assets in the company. Training and development are needed to have good resources to increase employee satisfaction and provide the best performance-one of the state-owned companies, namely PT. Hutama Karya has a policy in which a minimum of 5% of the total cost of Human Capital in 1 year must be budgeted for programs/activities in the fields of Learning and Development, as well as Research and Innovation. Therefore, this study analyzed the effect of training and development on employee performance mediated by worker satisfaction. The employees studied in this study were 301 employees at PT Hutama Karya, whose position is no more than manager level. Data was collected by distributing online questionnaires with answers using a Likert scale. This research is quantitative research, which was analyzed using the SEM-PLS method. The results of this study, namely training and development, respectively, have a direct positive and significant effect on employee job satisfaction; training and development, respectively, have an immediate positive and significant effect on employee performance; employee job satisfaction has a direct positive and significant impact on employee performance; and job satisfaction mediates training and development, respectively, positively, and significantly influence employee performance.